Gelation of covalently edge-modified laponites in aqueous media. 1. rheology and nuclear magnetic resonance - Patil, Suhas P.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Mahesh, T. S.; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2008)
We describe the covalent modification of the edges of laponite with organic groups and the influence of this modification on gelation behavior. We compare three materials: an unmodified laponite, a laponite edge modified with a trimethyl moiety (MLap), and an octyldimethyl moiety (OLap). Gelation is investigated using rheology and NMR T-1 relaxation measurements and nuclear Overhauser enhancement spectroscopy (NOESY). MLap and OLap show qualitatively different gelation. Gelation of MLap is very similar to laponite: MLap gels over the same time scale as laponite and has about the same solid modulus, and the MLap gel is almost as transparent as laponite. In contrast, OLap gels rapidly relative to laponite and forms a weak, turbid gel. We believe that gelation in laponite and MLap results from the formation of a network of well-dispersed platelets (or a few platelets), while in OLap, gelation results from a network of stacks of several platelets. NMR relaxation measurements indicate that gelation does not affect the average relaxation of water protons. However, T, increases marginally for the protons in the organic moieties in MLap and decreases for protons in the organic moieties in OLap. Relaxation measurements, analyses of line width, and NOESY taken together suggest that, in OLap, gelation is a consequence of association of the organic moieties on the laponite edges, and that this association strengthens with time. Thus, the time-dependent changes in NMR suggest a structural origin for the time-dependent changes in the rheological behavior.

Clickable SBA-15 mesoporous materials: synthesis, characterization and their reaction with alkynes - Malvi, Bharmana; Sarkar, Bibhas R.; Pati, Debasis; Mathew, Renny; Ajithkumar, Thalasseril G.; Sen Gupta, Sayam (Journal of Materials Chemistry, 2009)
SBA-15 mesoporous silica has been functionalized with azidopropyl groups through both one-pot co-condensation and post-synthetic grafting. For both these methodologies, azidopropyltriethoxysilane was used to introduce the azidopropyl groups. The azidopropyl modified SBA-15 material synthesized by one-pot co-condensation had hexagonal crystallographic order, pore diameters up of 50 angstrom, and the content of azidopropyl groups was found to be 1.3 mmol g(-1). The presence of the azidopropyl group was confirmed by multinuclear ((13)C, (29)Si) solid state NMR and IR spectroscopy. Both these materials underwent very efficient Cu(I)-catalyzed azide alkyne ``click'' reaction (CuAAC) with a variety of alkynes. Nearly 85% of the azide present in the SBA-15 material was converted to the corresponding triazole when propargyl alcohol was used as the substrate. This methodology was also used to incorporate mannose into SBA-15. Incubation of this mannose labeled SBA-15 with fluorescein labeled Concanavalin-A led to the formation of a fluorescent silica-protein hybrid material. The ease of synthesis for the azide labeled SBA-15 material together with its ability to undergo very efficient chemoselective CuAAC in water would make it a very attractive platform for the development of covalently anchored catalysts, enzymes and sensors.

MgCl2 center dot 4(CH3)(2)CHOH: a new molecular adduct and super active polymerization catalyst support - Thushara, K. S.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2009)
A new molecular adduct, MgCl(2 center dot)4(CH3)(2)CHOH, has been synthesized and characterized for structural aspects and demonstrated for super active ethylene polymerization activity with TiCl4 to ultrahigh molecular weight polyethylene in high yield.

Volume transition of PNIPAM in a nonionic surfactant hexagonal mesophase - Jijo, V. J.; Sharma, Kamendra P.; Mathew, Renny; Kamble, Samruddhi; Rajamohanan, P. R.; Ajithkumar, Thalasseril G.; Badiger, Manohar V.; Kumaraswamy, Guruswamy (Macromolecules, 2010)
We investigate the volume transition of a thermoresponsive polymer, poly(N-isopropylacrylamide), PNIPAM, in the presence of an aqueous solution of nonionic surfactant, C(12)E(9). We combine turbidimetry with optical microscopy, NMR, and SAXS to follow the volume transition of the PNIPAM and the H(1)-isotropic transition of the surfactant/water system. Nonionic surfactants such as C(12)E(9) are known to interact weakly with PNIPAM. Accordingly, we show that there is only a small change in the volume transition temperature for the PNIPAM in isotropic micellar solutions of C(12)E(9), even for relatively high concentrations of C(12)E(9). Interestingly, once the surfactant forms an H(1) phase, there is a dramatic decrease in the coil globule transition onset temperature. We believe that this behavior results from a competition between C(12)E(9) in the H(1) phase, and PNIPAM to associate with water. When PNIPAM in the H(1) phase is cooled to low enough temperatures so as to be in the coil state, it locally disturbs the hexagonal phase ordering. Thus, we show that for PNIPAM in a weakly interacting surfactant matrix, it is the phase behavior of the matrix rather than the matrix chemistry that governs the coil globule transition. Finally, we show that in a PNIPAM copolymer with a higher LCST we observe an interesting sequence of transitions in the surfactant phase: on cooling from a high temperature free-blowing turbid globular state (similar to 75 degrees C), we enter a free-flowing translucent coil phase (similar to 47 degrees C), then a turbid gel (similar to 25 degrees C) where the copolymer is collapsed in the HI phase, and finally a low-temperature clear gel (similar to 5 degrees C) where the copolymer is in the expanded coil state.

MgCl2 center dot 6PhCH(2)OH - a new molecular adduct as support material for ziegler-natta catalyst: synthesis, characterization and catalytic activity - Gnanakumar, Edwin S.; Thushara, K. S.; Bhange, Deu S.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Dalton Transactions, 2011)
Benzyl alcohol has been used to prepare a single phase MgCl2 center dot 6BzOH molecular adduct as a support for an ethylene polymerization catalyst (Ziegler catalyst). The structural, spectroscopic and morphological aspects of the MgCl2 center dot 6BzOH molecular adduct and the Ziegler catalyst have been thoroughly studied by various physicochemical characterization techniques. The presence of MgO6 octahedrons due to the interaction of Mg2+ with six -OH groups of the benzyl alcohol is confirmed from a Raman feature at 703 cm(-1), and structural studies. The supported catalyst activity has been evaluated for the ethylene polymerization reaction. The lower polymerization activity of the titanated Ziegler-Natta catalyst compared with a standard catalyst is attributed to the strong interaction of titanium chloride with the support and associated electronic factors.

Toward an understanding of the molecular level properties of ziegler-natta catalyst support with and without the internal electron donor - Thushara, K. S.; Gnanakumar, Edwin S.; Mathew, Renny; Jha, Ratnesh Kumar; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Sarma, Krishna; Padmanabhan, Sudhakar; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2011)
Two Ziegler-Natta catalysts supported on molecular adducts, namely, MgCl2 center dot 6EtOH (ME) and MgCl2 center dot 5EtOH center dot EtOOCPh (Est-ME), have been prepared. A systematic effort has been made to unravel the molecular level structure property relationships of the catalysts and adducts. Ethylbenzoate is an internal electron donor, and its in situ formation through EtOH+PhCOCl coupling is successfully achieved. The above adduct has been treated with TiCl4, and the resultant catalyst (Ti/Est-ME) is evaluated for ethylene polymerization activity. Rand C-13 CP/MAS NMR of Est-ME (Ti/Est-ME) show carbonyl features at 1730 (1680) cm(-1) and 169 (170) delta, respectively, providing direct support for the presence of ester as an integral part. In spite of low surface area, Ti/Est-ME gives higher yield for ethylene polymerization than the one derived from ME. The results indicate that electronic environment is more important than surface area or any other single factor in determining the polymerization activity.

Lamellar melting, not crystal motion, results in softening of polyoxymethylene on heating - Kumaraswamy, Guruswamy; Surve, Nikita S.; Mathew, Renny; Rana, Abhimanyu; Jha, Saroj K.; Bulakh, Neelima N.; Nisal, Anuya; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Ratnagiri, Ram (Macromolecules, 2012)
We probe temperature-dependent changes in the semicrystalline microstructure of polyoxymethylene using a combination of modulated DSC, SAXS, and solid-state NMR to characterize macroscopic behavior, lamellar-level structure, and molecular environments, respectively, and correlate these with the change in mechanical properties probed using DMA and AFM. Two model samples are investigated: a melt crystallized sample prepared by injection molding and a sample obtained by crystallization from dilute solution. Our investigations reveal that, for both samples, there is an increase in crystalline motions and in the amorphous content on heating. DMA and AFM measurements reveal that the modulus of the molded sample decreases on heating to about 100 degrees C; however, there is a significant difference in behavior of the solution crystals, where we observe no significant decrease in stiffness (from AFM measurements). Thus, in contrast to previous reports, we demonstrate that the decrease in modulus on heating polyoxymethylene does not correlate with chain motions in the crystalline regions. We use SAXS to probe the semicrystalline morphology for the samples on heating and show that, for the molded sample, there is a distribution of lamellar thickness at room temperature and that the thin lamellae in this distribution melt on heating. In contrast to the behavior of the melt crystallized samples, the solution crystals exhibit no change in the lamellar stacking on heating to 150 degrees C. We also demonstrate that, on heating, the amorphous regions in the solution crystals always appear to have restricted mobility while there are mobile and low mobility amorphous regions in the molded samples. Our results suggest that, contrary to conventional belief, the decrease in modulus on heating polyoxymethylene arises not from motions in the crystalline lamellae but primarily from melting of thin lamellae.

MgCl2 center dot 4((CH3)(2)CHCH2OH): a new molecular adduct for the preparation of TiClx/MgCl2 catalyst for olefin polymerization - Thushara, K. S.; Gnanakumar, Edwin S.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Dalton Transactions, 2012)
A new molecular adduct of MgCl2 with isobutanol, namely MgCl2 center dot 4((CH3)(2)CHCH2OH) (MgiBOH), has been prepared as a precursor to the supporting material for an olefin polymerization catalyst. The MgiBOH adduct and final titanated Ziegler-Natta catalysts have been thoroughly characterized by powder XRD, thermal analysis, Raman spectroscopy and solid-state NMR for structural and spectroscopy aspects. A peak observed at 712 cm(-1) in the Raman spectra of MgiBOH indicates the characteristic Mg-O-6 breathing mode and the formation of the adduct. The diffraction feature at 2 theta = 7.8 degrees (d = 11.223 angstrom) in the XRD confirms the adduct formation and the layered structure. The aim of the present article is to study how the insertion of a bulky isobutanol moiety affects the structural and electronic properties of the MgCl2 isobutanol molecular adduct. Indeed, the focus of the present study is to explore how the presence of isobutanol, in the initial molecular adduct, influences the final Z-N catalyst properties and its activity.